Tracing timing of growth in cultured molluscs using strontium spiking - de Winter, Niels J.; van Sikkeleras, Sterre; Goudsmit-Harzevoort, Barbara; Boer, Wim; de Nooijer, Lennart; Reichart, Gert-Jan; Claeys, Philippe; Witbaard, Rob (Frontiers in Marine Science, 2023)
Introduction Growth experiments present a powerful tool for determining the effect of environmental parameters on growth and carbonate composition in biogenic calcifiers. For successful proxy calibration and biomineralization studies, it is vital to identify volumes of carbonate precipitated by these organisms at precise intervals during the experiment. Here, we investigate the use of strontium labelling in mollusc growth experiments. Methods Three bivalve species (Cerastoderma edule, Mytilus edulis and Ostrea edulis) were grown under monitored field conditions. The bivalves were regularly exposed to seawater with elevated concentrations of dissolved strontium chloride (SrCl2). In addition, the size of their shells was determined at various stages during the experiment using calliper measurements and digital photography. Trace element profiles were measured in cross sections through the shells of these molluscs using laser ablation ICPMS and XRF techniques. Results Our results show that doses of dissolved strontium equivalent to 7-8 times the background marine value (~0.6 mmol/L) are sufficient to cause reproducible peaks in shell-incorporated strontium in C. edule and M. edulis shells. No negative effects were observed on shell calcification rates. Lower doses (3-5 times background values) resulted in less clearly identifiable peaks, especially in M. edulis. Strontium spiking labels in shells of O. edulis are more difficult to detect, likely due to their irregular growth. Discussion Strontium spiking is a useful technique for creating time marks in cultured shells and a reproducible way to monitor shell size during the growing season while limiting physical disturbance of the animals. However, accurate reconstructions of growth rates at high temporal resolution require frequent spiking with high doses of strontium.